Pemberdayaan Pengurus dan Jamaah Masjid Melalui Implementasi Sistem Informasi Manajemen Terpadu Berbasis Digital : Pengabdian - Syafran Nurrahman; Aep Saefullah; Farhat Abas; Tohiroh; Joned Ceilendra Saksana; Sitti Aliyah Azzahra; Elvira Sitna Hajar; Lena Farsiah; Zulkifli Zainudidin; Nurdin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Mosque management in Indonesia still faces challenges such as manual administration, lack of financial transparency, fragmented databases, and limited use of technology. This participatory seminar-based community service (PKM) aimed to empower mosque administrators in East Ciputat through integrated technology solutions. Conducted on July 19, 2025, the program included: (1) needs assessment via FGD and surveys, (2) technical training (Zoho Books, QRIS, PWA), (3) solution design workshops, and (4) follow-up mentoring. Ten key issues were identified, including digital resistance among senior administrators (65%) and low youth involvement. Solutions implemented included a cloud-based QRIS accounting system, a youth digital task force for social media, a centralized database with automated notifications, and a digital RKTM template. Results showed a 120% increase in youth donations, a 60% reduction in report preparation time, and a 45% rise in participation among 18–35-year-olds. The mosque’s digital transformation proved effective through gradual adoption and community mentoring. The study recommends forming a digital DKM forum and promoting data-driven collaboration with universities/government as an adoptable model for traditional mosques